Pengaruh Myofascial Release Terhadap Intensitas Nyeri Low Back Pain Myogenic pada Kelompok Tani Desa Maguan Kecamatan Ngajum Kabupaten Malang - Riska Jeje Nur'aini; Yohanes Deo Fau; Ahmad Abdullah; Rachma Putri Kasimbara (FORIKES, 2021)
Myogenic low back pain is a disorder of the lower back and surrounding muscles caused by musculoskeletal disorders or abnormalities without neurological disorders between the 12th thoracic vertebra to the bottom of the hip or anus. Myofascial release is a manual therapy technique that can reduce pain in myogenic low back pain because it makes the connective tissue more flexible between muscles and bones. Qualitative research method experimental pre and post test one group design using 15 people as respondents who met the criteria were randomly selected to be treated in the form of myofascial release dose of 10 15 minutes / treatment 2 times a week for 1 month. The results of the low back pain myogenic pain intensity before and after the intervention were 5.2 (5.8 – 7.2) to (0.2 – 2.4) with a p value of 0.001. It can be concluded in this study that myofascial release has an effect on reducing the intensity of low back pain myogenic pain in farmer groups in Maguan Village, Ngajum District, Malang Regency.Keywords: low back pain myogenic; myofascial release; pain intensityABSTRAKLow back pain myogenic merupakan gangguan pada otot daerah pinggang bawah dan sekitarnya yang disebabkan oleh gangguan atau kelainan unsur muskuloskeletal tanpa disertai gangguan neurologis antara vertebra thorakal 12 sampai dengan bawah pinggul atau anus. Myofascial release adalah teknik terapi manual yang dapat mengurangi nyeri pada low back pain myogenic karena membuat jaringan ikat lebih fleksibel atara otot dan tulang. Metode penelitian kualitatif experimental pre dan post test one group design menggunakan 15 orang sebagai responden yang memenuhi kriteria dipilih secara acak dilakukan perlakuan berupa myofascial release dosis 10- 15 menit/treatment sebanyak 2 kali dalam seminggu selama 1 bulan. Didapatkan hasil intensitas nyeri low back pain myogenic sebelum dan sesudah intervensi sebesar rerata 5,2 (5,8-7,2) menjadi (0,2-2,4) dengan nilai p 0,001. Dapat disimpulkan dalam penelitian ini bahwa myofascial release berpengaruh dalam menurunkan intensitas nyeri low back pain myogenic pada kelompok tani di Desa Maguan Kecamatan Ngajum Kabupaten Malang.Kata kunci: low back pain myogenic; myofascial release; intensitas nyeri